Sharof Rashidov is a strong statesman - Suyarova Aynura Ibodullayevna (Genius Journals, 2022)
The article provides information about the powerful policy and activities of a powerful statesman Sharof Rashidov. This article seeks to fully disclose Sharof Rashidov's activities as a political statesman.
Keywords: Sharof Rashidov; Uzbekistan; powerful statesman; Red Party